2007
DOI: 10.1270/jsbbs.57.271
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationship of Wild and Cultivated Vigna (Subgenus Ceratotropis, Fabaceae) from Myanmar Based on Sequence Variations in Non-coding Regions of trnT-F

Abstract: For clarifying the phylogenetic diversity of fifteen species of the subgenus Ceratotropis, including seven wild and three cultivated Vigna species collected from Myanmar, sequence variations in three trnT-F non-coding regions of the chloroplast genome were analyzed. The Myanmar materials were clustered into two well differentiated groups, the azuki bean group and the mung bean group. Six Myanmar species were clustered into the azuki bean group, and four species into the mung bean group. The azuki bean group co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…Results from the cluster analysis revealed that all the genotypes of Asian Vigna could be clearly differentiated and classified into two groups; mungbean group and azuki bean group (Figure 2). The results were in agreement with previous studies using non-coding sequences of trn T-F [42,43]. In contrast, studies using AFLP [44], rDNA-ITS and atp B- rbc L sequences [45] recognized three groups within the Asian Vigna .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Results from the cluster analysis revealed that all the genotypes of Asian Vigna could be clearly differentiated and classified into two groups; mungbean group and azuki bean group (Figure 2). The results were in agreement with previous studies using non-coding sequences of trn T-F [42,43]. In contrast, studies using AFLP [44], rDNA-ITS and atp B- rbc L sequences [45] recognized three groups within the Asian Vigna .…”
Section: Resultssupporting
confidence: 92%
“…In contrast, studies using AFLP [44], rDNA-ITS and atp B- rbc L sequences [45] recognized three groups within the Asian Vigna . In addition, it is worth noting that V. nepalensis , which has similar morphology [46] and close genetic relationship with V. angularis [43,45], was found to be highly distinct in our study. V. grandiflora previously shown to have high morphological and genetic similarity to V. radiata [46,47] was found to have closer genetic relationship with V. trilobata and V. stipulacea than V. radiate in this study.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…The sectional classification of subgenus Ceratotropis was confirmed by several researchers (Jaaska and Jaaska, 1990;Kaga et al, 1996;Doi et al, 2002;Konarev et al, 2002;Tomooka et al, 2002aTomooka et al, , 2002bSaini et al, 2008). Moreover, morphological studies and molecular approaches have been used efficiently for the taxonomy of the subgenus Ceratotropis (Verdcourt, 1970;Maréchal et al, 1978;Egawa and Tomooka, 1994;Lawn, 1995;Tateishi, 1996;Doi et al, 2002;Goel et al, 2002;Tateishi and Maxted, 2002;Tomooka et al, 2002b;Bisht et al, 2005;Tun and Yamaguchi, 2007;Saini et al, 2008;Saini and Jawali, 2009;Vir et al, 2010;Dixit et al, 2011;Javadi et al, 2011;Aitawade et al, 2012;Latha et al, 2014;Yadav et al, 2014).…”
Section: Introductionmentioning
confidence: 92%
“…; Yano et al . ; Tun & Yamaguchi ; Javadi et al . ) and DNA amplification fingerprinting (Simon et al .…”
Section: Introductionmentioning
confidence: 99%